Human Uniqueness from a Biological Point of View - Reich, David 1974- (2023)
This article seeks to provide some genetic perspectives on the question “Just How Special Are Humans—Really?” It begins with an introduction to how genetic variation can provide information about the past. It continues by discussing two ways in which genetic analyses has, on multiple occasions, shown that humans are less unique than we thought we are. We have a cognitive bias to toward thinking we are special. Our species has colonized an ecological niche not exploited by any other species on our earth, but how much of our adaptation to that niche is cultural rather than genetic?
Keywords: human uniqueness; genetic evolution; Cultural Evolution; Biology